Variations of technical actions among playing positions in male high level volleyball - Lima, Ricardo Franco; Caleiro, Francisco; Clemente, Filipe Manuel (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Volleyball is a team sport in which a mistake made by a player on one team gives a point to the opponent. This fact requires coaches to think of all volleyball skills as having the same level of importance. Aim of Study. The purpose of this study was to analyze and compare variations of the technical actions of players’ in-game role in terms of total points, breaking points, and the point/error relationship during one professional season. Material and Methods. The study included 80 matches played by 14 teams participating in the male First Division Portuguese Championship during the 2017/2018 season. The study analyzed 295 sets with a total of 85,233 actions. Data was collected using the statistical programs Data Volley and Click & Scout after video recording the matches. Results. Considering breaking points, moderate decreases were found for middle blockers vs opposites, and small increases were found for outside hitters vs middle blockers. Also, small increases were found for outside hitters vs opposites. Considering the point/error relationship, small decreases were found for middle blockers vs opposites and for outside hitters vs opposites. Trivial differences were found between outside hitters and middle blockers. Conclusions. The main differences portrayed in the study show that to have success, during practice, coaches need to focus on improving players’ efficiency in different game actions in the counter-attack phase.
Keywords: match analysis; player role; elite players; notational analysis; performance